2003
DOI: 10.1080/00015458.2003.11679423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Refinement of Surgical Technique and Surgeon’s Experience on the Rate of Complications after Total Thyroidectomy for Benign Thyroid Disease

Abstract: Complications of total thyroidectomy can be minimized with increasing experience and the refinement of surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…summarizes the study selection process. The characteristics of included studies are shown in Table S1 (supporting information). Of the 115 observational studies included, 61 were prospective and 55 retrospective; one study had both prospective and retrospective components.…”
Section: Resultsmentioning
confidence: 99%
“…summarizes the study selection process. The characteristics of included studies are shown in Table S1 (supporting information). Of the 115 observational studies included, 61 were prospective and 55 retrospective; one study had both prospective and retrospective components.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 43 selected studies are shown in Table I through Table III 8–51. Baseline characteristics are provided in Table IV.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, laryngeal nerve function was evaluated with postoperative nasopharyngoscopy and subjective assessment of vocal fold movements. The evaluation of vocal fold movement depends on the material used (videolaryngostroboscopy) and the surgeon experience and may, therefore, report low-to-moderate interrater reliability [ 36 , 37 ]. In practice, it is recommended to assess voice quality through videolaryngostroboscopy, subjective and objective voice evaluations [ 38 ], a combination of which was performed in only a few studies [ 14 , 16 , 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%